Kintsugi flap in the management of giant mandibular ameloblastoma: A case report (Indian Journal of Case Reports, 2020)
Neglected ameloblastomas may present with massive swelling of the jaw. Reconstruction of intraoral mucosal and floor of the mouth defects following surgical resection of the tumors is always a challenge. However, it is not possible for all patients due to various reasons which include a medical status that precludes an extended operative procedure, history of coagulopathy, connective tissue disorders, vasculitis, peripheral vascular disease, venous insufficiency, and the second surgical site. Reconstruction of the mandible with titanium plate is commonly practiced for those patients. We report the case of giant ameloblastoma measuring approximately 14 cm × 13 cm × 10 cm, involving the right side of the mandible crossing midline up to the left body of the mandible. The tumor was excised and the mandibular defect was reconstructed with titanium plate fixed. The purpose of this article is to propose a possibility of using the redundant tumor-free skin and subcutaneous tissue as a local cutaneous flap for the reconstruction of the floor of the mouth and as a soft tissue draping for the titanium plate. The technique has the advantage of avoiding a second surgical site and has no donor site morbidity. Being done as a single-stage procedure, it eliminates the need for revision of the flap, thereby avoiding multiple surgeries.